Performance of a solar assisted solid desiccant dryer for kenaf core fiber drying under low solar radiation. (February 2015) - Misha, S.; Mat, S.; Ruslan, M.H.; Salleh, E.; Sopian, K.
Highlights: The solar dryer system can be operated even at low solar radiation. The drying process continues during off-sunshine hours. The dryer system can dry products at high volume and produces uniform drying. The air velocity is more significant at the earlier stage of the drying process. Temperature is more important as the moisture content of the product decreases. Abstract: The solar assisted solid desiccant dryer was used to dry kenaf core fiber at low solar radiation. The solar energy was used to heat water using solar collector and transfer heat to the air via heat exchanger. The hot air is used for regeneration of desiccant wheel and increase temperature of process air after dehumidification. The desiccant wheel system is used as a heat source to supply hot and dry air for the drying chamber. Drying under the sun was also conducted simultaneously for comparison. The main objective of this paper is to study the performance of a dryer. The drying time using this system was reduced by 24% from 20.75 h to 15.75 h compared to open sun drying because the process continues even in the absence of sunshine using the dryer system. Dryer efficiency at low solar radiation (average 394 W/m 2 ) is approximately 12%. The percentage of solar energy used in this system is approximately 44% from the overall energy. During hot sunny days, the solar energy percentage should be higher and the temperature of drying air would also increase. Thus, drying performance also increases under high solar radiation. The uniformity of the drying process throughout the drying chamber was acceptable because the sample on the five random trays achieved final moisture content below 18% in two days. In the initial stages of removing moisture on the product surface, air velocity is more significant than air temperature and humidity. As the moisture content of the product decreases, air temperature is more important to move the water from the interior to the surface for evaporation. The result shows that the solar-assisted solid desiccant dryer can continue to be operated even at low solar radiation for kenaf core fiber drying. The improvement in performance of other components such as solar collector, heat exchanger, and desiccant wheel will also improve overall drying performance.